The Effect of Work Atmosphere and Job Training on Employee Retention: A Test of Multigroup Moderated Mediation Effect - Natasya Putri Salsabilla; Vivin Maharani Ekowati (Universitas Negeri Padang, 2025)
This research evaluates how the work atmosphere and job training influence employee retention in the restaurant sector in Malang City, with job satisfaction as a mediator and intrinsic motivation as a moderator. Adopting a quantitative explanatory design, the study employs the SEM-PLS analysis technique via SmartPLS 4. Primary data were gathered through questionnaires distributed to 149 employees chosen using a proportional stratified random sampling method. The findings indicate that the work atmosphere does not significantly affect employee retention, whereas job training does. Furthermore, job satisfaction serves as a mediator linking both work atmosphere and training to employee retention. Conversely, intrinsic motivation did not moderate the relationship between training and retention. Consequently, the study highlights the need to foster a supportive work environment, implement practical training, and boost job satisfaction to enhance staff retention in the restaurant service industry.